Structure of the elongating ribosome: Arrangement of the two tRNAs before and after translocation - Nierhaus, Knud H. (The National Academy of Sciences, 1998)
The ribosome uses tRNAs to translate the genetic information into the amino acid sequence of proteins. The mass ratio of a tRNA to the ribosome is in the order of 1:100; because of this unfavorable value it was not possible until now to determine the location of tRNAs within the ribosome by neutron-scattering techniques. However, the new technique of proton-spin contrast-variation improves the signal-to-noise ratio by more than one order of magnitude, thus enabling the direct determination of protonated tRNAs within a deuterated ribosome for the first time. Here we analyze a pair of ribosomal complexes being either in the pre- or post-translocational states that represent the main states of the elongating ribosome. Both complexes were derived from one preparation. The orientation of both tRNAs within the ribosome and their mutual arrangement are determined by using an electron microscopy model for the Escherichia coli ribosome and the tRNA structure. The mass center of gravity of the (tRNA)(2)mRNA complex moves within the ribosome by 12 ± 4 Å in the course of translocation as previously reported. The main results of the present analysis are that the mutual arrangement of the two tRNAs does not change on translocation and that the angle between them is, depending on the model used, 110° ± 10° before and after translocation. The translocational movement of the constant tRNA complex within the ribosome can be described as a displacement toward the head of the 30S subunit combined with a rotational movement by about 18°.